(untitled) (TAMADDUN NURI JURNALI, 2024)
This article, based on scientific data, highlights the history of the specialized lyceum, boarding school 164 of the Karakol district of the Bukhara region, material support, and pedagogical activities of the winners of the republican and world Olympiads of this school.